Impedance Spectroscopy as a Tool for Monitoring Performance in 3D Models of Epithelial Tissues - Gerasimenko, Tatiana; Nikulin, Sergey; Zakharova, Galina; Poloznikov, Andrey; Petrov, Vladimir; Baranova, Ancha; Tonevitsky, Alexander (Frontiers in Bioengineering and Biotechnology, 2020)
In contrast to traditional 2D cell cultures, both 3D models and organ-on-a-chip devices allow the study of the physiological responses of human cells. These models reconstruct human tissues in conditions closely resembling the body. Translation of these techniques into practice is hindered by associated labor costs, a need which may be remediate by automation. Impedance spectroscopy (IS) is a promising, automation-compatible label-free technology allowing to carry out a wide range of measurements both in real-time and as endpoints. IS has been applied to both the barrier cultures and